2017
DOI: 10.1002/ajp.22719
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment for the endangered black lion tamarinLeontopithecus chrysopygus(Mikan, 1823),Callitrichidae, Primates

Abstract: This is the first study analyzing genetic diversity in captive individuals of the endangered black lion tamarin, Leontopithecus chrysopygus, and also comparing genetic diversity parameters between wild populations and captive groups using the same set of molecular markers. We evaluated genetic diversity and differentiation for the Brazilian and European captive groups and a wild population through 15 polymorphic microsatellite markers. The genetic diversity levels were similar among Brazilian captive, European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Genetic studies with lion tamarins differ in the number of samples, populations and microsatellite loci, and in the type (skin, blood or hair) and origin (wild life or captivity) of samples, making it difficult to compare them. Considering these differences, the mean expected heterozygosity for GHLT was similar to that observed for Leontopithecus rosalia [Grativol et al, 2001;Moraes et al, 2017] and not much higher than the values reported for Leontopithecus caissara [Martins and Galetti, 2011;Martins et al, 2012] and L. chrysopygus [Ayala-Burbano et al, 2017]. The average number of alleles was relatively high for GHLTs in the wild, but this might be (partially) due to differences in sample sizes (for which this parameter is relatively sensitive).…”
Section: Genetic Diversitymentioning
confidence: 82%
See 1 more Smart Citation
“…Genetic studies with lion tamarins differ in the number of samples, populations and microsatellite loci, and in the type (skin, blood or hair) and origin (wild life or captivity) of samples, making it difficult to compare them. Considering these differences, the mean expected heterozygosity for GHLT was similar to that observed for Leontopithecus rosalia [Grativol et al, 2001;Moraes et al, 2017] and not much higher than the values reported for Leontopithecus caissara [Martins and Galetti, 2011;Martins et al, 2012] and L. chrysopygus [Ayala-Burbano et al, 2017]. The average number of alleles was relatively high for GHLTs in the wild, but this might be (partially) due to differences in sample sizes (for which this parameter is relatively sensitive).…”
Section: Genetic Diversitymentioning
confidence: 82%
“…In addition, these similar genetic diversities among captive populations and our results were found even using different types of samples: skin (n = 29, loci = 9, N a = 3.67, H e = 0.59 [Galbusera and Gillemot, 2008]), blood (n = 55, loci = 16, N a = 5.1, H e = 0.65) and hair (n = 49, loci = 16, N a = 4.6, H e = 0.55) [Orefice, 2015]. The importance of genetically diverse captive populations for the conservation of lion tamarin species with markedly smaller wild populations has also been documented [Ayala-Burbano et al, 2017;Moraes et al, 2017]. In the case of L. rosalia, the captive population contributed greatly to the wild population by means of a reintroduction programme [Kierulff et al, 2012;Moraes et al, 2017].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…However, this is not an easy task, and consequently captive groups tend to present lower levels of genetic diversity and higher inbreeding rates than expected 2,7 , challenging the success of these captive breeding programs. On the other hand, wild endangered species often present small and fragmented populations subjected to bottleneck effects and absence of gene flow, and low genetic diversity levels are commonly also observed in nature 8,9 . This is the case for the black-lion-tamarin (BLT), Leontopithecus chrysopygus (Callitrichidae, Platyrrhini), an endangered primate inhabiting exclusively the Atlantic Forest of São Paulo state in Southeast Brazil 8,10 .The population size of L. chrysopygus in nature is small 11 , currently estimated at a total of a thousand individuals living in a few small forest fragments 12 .…”
mentioning
confidence: 99%
“…The animals kept at Jersey Zoo successfully produced offspring, and some L. chrysopygus were transferred to other institutions in Europe, North America and Australia. However, the majority of these individuals died 17 , and nowadays there are only extant captive BLT overseas in Jersey 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation